2014
DOI: 10.1002/2327-6924.12082
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge translation: A Nurse Practitioner Clinical Ladder Advancement Program in a university-affiliated, integrated medical center

Abstract: Purpose A Nurse Practitioner Clinical Ladder (NPCL) Advancement Program was designed to recognize and reward advanced nursing practice and promote nurse practitioner (NP) retention at New York University Hospitals Center (NYUHC). Data sources Search of published and gray literature was conducted. Electronic databases included CINAHL, Medline, PubMed, Cochrane Library of Systematic Reviews, and the Joanna Briggs Institute. Conclusions The NYUHC NPCL Advancement Program incorporated its current Staff Nurse Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
(27 reference statements)
1
23
0
Order By: Relevance
“…Wood et al (2021) also indicated that NPs with higher advancement levels tend to perceive greater professional identity and higher support for the role, which promotes job satisfaction. NPs are recognized and compensated for their clinical excellence and increased productivity, positively affecting job satisfaction and patient outcomes (Paplanus et al, 2014). Organisations could create an advanced career ladder, providing opportunities for the professional growth of NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Wood et al (2021) also indicated that NPs with higher advancement levels tend to perceive greater professional identity and higher support for the role, which promotes job satisfaction. NPs are recognized and compensated for their clinical excellence and increased productivity, positively affecting job satisfaction and patient outcomes (Paplanus et al, 2014). Organisations could create an advanced career ladder, providing opportunities for the professional growth of NPs.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of job performance, these can be the actions and behaviours of individuals that contribute to organizational goals (Rotundo, 2002;Wong & Laschinger, 2013). It can relate more to personal effectiveness when increased self-efficacy, high motivation, increased organizational commitment, lowered burnout level, increased autonomy, decreased occupational stress, increased job satisfaction, organizational commitment, and authentic leadership are noted; or more broadly, work effectiveness when achievement and successes, respect and cooperation in the organization alongside client satisfaction take place (Cicolini, Comparcini, & Simonetti, 2014;Cowden & Cummings, 2012;Flinkman et al, 2017;Goedhart et al, 2017;Li et al, 2018;Numminen, Repo, & Leino-Kilpi, 2017;Paplanus, Bartley-Daniele, & Mitra, 2014;Rosser et al, 2017;Saber, 2014;Wong & Laschinger, 2013). Two important aspects of performance we focus on in the present review are organizational commitment and job satisfaction.…”
Section: Organizational Performancementioning
confidence: 99%
“…A professional career stage is a system to improve performance and professionalism, field-based competency [4], work satisfaction and resolve differences in the amount of remuneration workers believe they deserve [5]. The success of a career depends on the nurse’s participation in clinical decision making, the ability to define short-term and long-term goals and the ability to manage his or her nursing career proactively [6]. Nurses must realise that they need to improve their competence, while their leaders need to accept their responsibility to facilitate this process and support the nurses with developmental policies [7].…”
Section: Introductionmentioning
confidence: 99%